Analisis Penerimaan Cryptocurrency dan Instrumen dengan Menggunakan Unified Theory of Acceptance dan Use of Technology (UTAUT) - Fernand William Citra; Ade Maulana (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
Cryptocurrency is one of the recent innovation and technological instrument that begins with the invention of Bitcoin in 2009. The Unified Theory of Technology Acceptance or UTAUT framework for short, is one of the model available to use regarding technological acceptance by mankind. The UTAUT framework is used to describe what might push somebody to accept and use new technologies based on available varia bles given by default by the framework. Using UTAUT’s model, we can design questions on a questionnaire based directly on those available variables. This research is done with the goal of knowing what actually motivate the citizen of Medan to accept and use cryptocurrency in their lives. Using 87 data collected from questionnaire, with 30 used as sample for data testing and the remaining 57 for data training on SPSS Statistics 25, an application developed by IBM Corp. (International Business Corporation), we will find out about validity, reliability, normality, and linear regression. The results obtained of those data are valid and reliable, with the variable of Y being affected by the variable of X1 and X4, while X2 and X3 do not, and 14.9% of those variabl e variations affect Y, while 85.1% were external variables not included in this research.